2002
DOI: 10.1051/agro:2002013
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of rhizobia isolated from chickpea (Cicer arietinum) growing in Moroccan soils

Abstract: Phenotypic characteristics of fifty-six rhizobia strains isolated from root nodules of two chickpea (Cicer arietinum L.) cultivars, growing in soils collected from different areas of Morocco, were studied. Tolerance to salinity, high temperatures, acid and alkaline pHs, heavy metals and to antibiotics as well as symbiotic and cultural characteristics allowed the description of a wide physiological diversity among tested isolates. Numerical analysis of the phenotypic characteristics showed that, below the bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 19 publications
4
19
1
Order By: Relevance
“…Monosaccharides and sugar alcohols (D-glucose, D-fructose, galactose, sorbitol and inositol) were poorly utilized by most test isolates, whereas, disaccharides (sucrose and maltose) were assimilated by most of them. Thus, they are in line with what reported by others for chickpea rhizobia [47]. Few isolates in different groups were used starch as a carbon source, but with exception of separate isolates and one isolate in group 3, all other groups were failed to use cellulose.…”
Section: Symbiotic and Phenotypic Characteristics Of Rhizobia Nodulaisupporting
confidence: 91%
“…Monosaccharides and sugar alcohols (D-glucose, D-fructose, galactose, sorbitol and inositol) were poorly utilized by most test isolates, whereas, disaccharides (sucrose and maltose) were assimilated by most of them. Thus, they are in line with what reported by others for chickpea rhizobia [47]. Few isolates in different groups were used starch as a carbon source, but with exception of separate isolates and one isolate in group 3, all other groups were failed to use cellulose.…”
Section: Symbiotic and Phenotypic Characteristics Of Rhizobia Nodulaisupporting
confidence: 91%
“…Isolates grown on the Streptomycin showed very less tolerance with respect to concentration. Several studies reported the existence of broad variation among chickpea rhizobia with respect to the fate of their intrinsic antibiotics resistance (Maâtallah et al, 2002;Kucuk and Kıvanc, 2008). The isolates' sensitivity to antibiotics may be due to inability to resist exposed toxicity with less adaptation in natural environments (Singh and Bamania, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Tolerance of the isolates to extreme temperature, pH, and salt was checked according to Maatallah et al (2002). Intrinsic antibiotics resistance (IAR) of isolates to Kanamycin sulfate, Streptomycin sulfate, Chloramphenicol, Ampicillin, Neomycin sulfate and Erythromycin with concentration of (μg/ml ) 2.5, 5, and 10 was tested.…”
Section: Stress Tolerance Testmentioning
confidence: 99%